IFRS adoption and real earnings management in Bangladesh: The role of board characteristics - Mohammad Tariq Hasan; Md. Kaium Hossain; Mohammad Sarwar Rekabder; Mohammad Shahansha Molla; Abu Sadat Muhammad Ashif (Cogent Business & Management, 2022)
The adoption of the international financial reporting standard (IFRS) has become an important research topic and received considerable attention from many empirical researchers worldwide. However, to the best of the authors' knowledge, it's one of the very few efforts to examine the relationship between IFRS adoption and real earnings management (REM) with the moderating role of board characteristics (board size, independence, expertise, CEO duality, and gender diversity). The study employs 94 firms listed on the Dhaka Stock Exchange (DSE) for six years, i.e., 564 firm year's observations, over two time periods as pre (2004-06) and post (2013/14-15/16) adoption of IFRS. The underpinning theory of the study is agency theory, which explains the relationship among variables. To perform regression analysis on balanced panel data, STATA was used with PCSE estimators. The results show that IFRS has a significant negative relationship with REM. Board expertise and gender diversity have a significant negative relationship with REM, whereas CEO duality has a significant positive association with REM. Moreover, it is documented that board size and CEO duality have a significant negative moderating effect on the relationship between IFRS and REM. In contrast, board expertise, board independence, and gender diversity have significant positive moderation. It implies that a strong corporate governance mechanism may help to attain the objectives of IFRS adoption in Bangladesh. Thus, the findings of this study may persuade regulatory authorities in Bangladesh to make corporate governance compliance mandatory with punitive action, which would also act as a guideline for developing countries.
Keywords: G34; M40; M41; 650; Bangladesh; board characteristics; Dhaka stock exchange; IFRS adoption; real earnings management